Factors Associated with Male Partner Support During Pregnancy and Child Birth in Kabale District. - Niwarinda, Denesi (Kabale University, 2024)
Background: Pregnancy and childbirth are natural processes but by no means risk-free. Efforts to improve maternal and child health services have been made, but poor outcomes of pregnancy and child’s birth remain high in Sub-Saharan Africa. The study sought to assess factors associated with male partner support during pregnancy and childbirth in selected public and faith-based health facilities in Kabale district in Uganda. Methods: The study employed a descriptive cross-sectional design using a quantitative approach to assess 318 mothers using a convenience sampling method. Both predictor variables including health facility service factors, social-cultural factors, and demographics as well as support as an outcome were assessed using a semi-structured questionnaire. Quantitative data generated from the field was analyzed using descriptive and inferential statistics and presented in frequencies and percentages, and logistics regression was used to trace the associations between study variables and male partner support during pregnancy and childbirth at a 0.05 level of significance. Results: The main findings of the study indicate that 216/318 (68%) had low male partner support during pregnancy and childbirth and only 102(32%) had high male partner support during pregnancy and childbirth. The study found a significant association between health-related factors and the support women receive from their male partners (OR=1.16, 95%CI: 1.08 to 1.25, p<0.001). Additionally, contextual / social-cultural-related factors were also significantly associated with the support women received from their male partners during pregnancy and childbirth (OR=1.19 95%CI: 1.03c to 1.38, p=0.017). Conclusion: The study recommends building the capacity of health workers on male support, prioritizing the adoption of a resource package for engaging men in pregnancy and childbirth and its implementation, awareness through outreaches and media, incentives at each facility for male partners support and community engagement on male support in pregnancy and childbirth.